Meningkatkan Kompetensi Kepala Sekolah dalam Menganalisis Raport Mutu Sekolah Melalui Supervisi Manajerial Metode Workshop - Murniyati Murniyati (Vidya Karya, 2021)
This research aimed to improve the competence of school principals in target elementary schools in analyzing the quality of schools report cards based on National Education Standards (SNP) through managerial supervision by the workshop method. The method used in this research was school action research through two cycles. The subjects of this study were seven elementary school principals in the target area of the North Tapin sub-district, Tapin Regency. The instruments used in this study were the analysis table worksheet and the preparation of recommendations for the quality mapping results, and the supervision implementation sheet. Data were analyzed descriptively quantitative. The results showed: (1) 28.57% of the target school principals completed individually and 64.29% completed classically in the first cycle; (2) 100% of the target school principals have completed individually and 85.71% have completed classically in cycle II. Based on the research results, the managerial supervision by workshop method could improve school principals' competence in analysing school quality report cards based on SNP in the education units.Keywords: Report; School principals; Supervision; WorkshopTujuan penelitian ini adalah meningkatkan  kompetensi kepala sekolah di Sekolah Dasar (SD) binaan dalam menganalisis raport mutu sekolah berbasis Standar Nasional Pendidikan (SNP) melalui supervisi manajerial metode workshop. Metode yang digunakan dalam penelitian ini adalah penelitian tindakan sekolah melalui dua siklus. Subjek penelitian ini adalah tujuh orang kepala sekolah SD di wilayah binaan kecamatan Tapin Utara Kabupaten Tapin. Instrumen yang digunakan dalam penelitian ini adalah lembar kerja tabel analisis dan penyusunan rekomendasi terhadap hasil pemetaan mutu, dan lembar pelaksanaan supervisi. Data dianalisis secara deskriptif kuantitatif. Hasil penelitian menunjukkan: (1) 28,57% kepala sekolah binaan tuntas secara individu dan 64,29% tuntas secara klasikal pada siklus I; (2) 100% kepala sekolah binaan tuntas secara individu dan 85,71% tuntas secara klasikal pada siklus II. Berdasarkan hasil penelitian tersebut supervisi manajerial metode workshop dapat meningkatkan kompetensi kepala sekolah dalam menganalisis raport mutu sekolah berbasis SNP di satuan Pendidikan.Kata Kunci: Raport; Kepala Sekolah; Supervisi; Workshop